The role of Tumor necrosis factor alpha −308 G>A promoter polymorphism in pediatric community acquired pneumonia - Fady M. El Gendy; Muhammad Said El-Mekkawy; Sherin Sobhy El-Naidany; Shimaa Tarek El-torgoman (SpringerOpen, 2020)
Abstract Background Tumor necrosis factor alpha (TNF-α) −308 G>A promoter polymorphism might be associated with excessive production of the proinflammatory cytokine TNF-α, modulating host response to pulmonary infections. Our objective was to evaluate the association of TNF-α gene −308 G>A polymorphism with susceptibility to, and severity of, community-acquired pneumonia (CAP). Results This was a cross-sectional study including 45 Egyptian children hospitalized for CAP in addition to 45 healthy children who served as a control group. Pneumonia severity was assessed on admission by the World Health Organization (WHO) guidelines; Pediatric Respiratory Severity Score (PRESS) score; Predisposition, Infection, Response and Organ failure (PIROm) score; and Respiratory Index of Severity in Children (RISC) score. Genotyping of TNF-α polymorphism was performed to all individuals by polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP). Patients were monitored till hospital discharge. Frequency of AG genotype was lower among patients compared with control [odds ratio (OR) and 95% confidence interval (CI) = 0.13 (0.03-0.63); p = 0.012]. Prevalence of genotypes AA+AG was lower among patients compared with controls [OR and 95% CI = 0.34 (0.12-0.99); p = 0,048]. The "A" allele prevalence was higher among controls, but no significant association was found with CAP [OR and 95% CI = 0.58 (0.25-1.35); p = 0.21]. When PRESS score was used to classify patients into "severe pneumonia" and "non-severe pneumonia," no significant association of any of the alleles or genotypes with CAP severity was found. Conclusion TNF-α −308 G>A polymorphism confers protection from pediatric CAP but is not associated with indicators of CAP severity. Larger studies are needed to confirm these findings in pediatric patients from different ethnicities.